Spectroscopic Characterisation of Naples Yellow Variations in Paintings from the Turn of the 20th Century - Antušková, Václava; Šefců, Radka; Šulcová, Petra; Dohnalová, Žaneta; Luxová, Jana; Kmoníčková, Martina Bajeux; Turková, Ivana; Kotrlý, Marek (John Wiley & Sons Ltd., 2023)
The research presented in this study aimed to document the variability of synthetic lead antimonate pigments known as Naples yellow in selected artworks by Czech landscape painters from the turn of the 20th century. Spectra obtained through Raman spectroscopy show considerable difference in the position of main band maximum (from 110 to 145 cm(-1)) characteristic of cubic pyrochlore structure Pb2Sb2O7 – the major phase of the Naples yellow pigment. In several samples, hexagonal PbSb2O6 with main band at 655 cm(-1) was identified as a dominant phase, a finding that is somewhat surprising because PbSb2O6 has been generally considered a minor admixture to cubic Pb2Sb2O7. Reference pigment samples were synthesised under known conditions, and their spectra were collected in order to get more comparative material. Also, commercially available Naples yellow pigments were characterised in the same way. We observed considerable differences of the obtained spectra caused by the presence of admixtures and diverse production conditions. The diversity of Naples yellow and the corresponding Raman spectra makes their identification problematic. Presented data thus may serve as a reference material in the identification process.
Spektroskopická charakterizace variací neapolské žluti v malbách z přelomu 20. století
Keywords: 19th century painting; Naples yellow; Pigment identification; Rosiaite; Malba 19. století; neapolská žluť; identifikace pigmentu; rosiait